Familial caregivers' experiences with home‐visit nursing for persons with dementia who live alone. Issue 1 (30th July 2018) - Kitamura, Tatsuru; Tanimoto, Chie; Oe, Shingo; Kitamura, Maki; Hino, Shoryoku
Abstract : Aim: The Japanese Comprehensive Strategy to Accelerate Dementia Measures, known as the New Orange Plan, aims to support people with dementia living in their communities. Home‐visit nurses (HVN) are expected to play an important role in this comprehensive support system. In this preliminary study, we explored caregivers' experiences before and after implementation of HVN care for persons with dementia who lived alone. Methods: This study was a qualitative descriptive design using in‐depth interviews with five family caregivers of persons with dementia who lived alone while receiving HVN. Thematic content analysis was undertaken. Results: Before receiving HVN, caregivers experienced anxiety and embarrassment due to the occurrence of dementia symptoms, and they also experienced considerable isolation and anguish after hearing the diagnosis. After initiating HVN, caregivers gained a feeling of security and an alleviation of psychological stress. They also gained a deeper understanding of the disease and appropriate care for dementia patients. Notably, caregivers perceived not only positive changes in themselves, but also in the recipients, such as improvements in symptoms and quality of life. Finally, caregivers realized that people with dementia can live alone if appropriate services are provided. Conclusion: HVN can have a positive impact on family caregivers involved in dementia care, as well as on the recipients' psychological status. Overall, the experience of HVN made the family caregivers more positive about home care for their family member with dementia. Although further case studies are needed to make definitive conclusions, we believe that HVN could play a key role in the forthcoming New Orange Plan.